Crystal structure and catalytic activity of the PPM1K N94K mutant. Issue 4 (3rd January 2019) - Dolatabad, Meisam Rostaminasab; Guo, Lu‐lu; Xiao, Peng; Zhu, Zhongliang; He, Qing‐tao; Yang, Du‐xiao; Qu, Chang‐xiu; Guo, Sheng‐chao; Fu, Xiao‐lei; Li, Rui‐rui; Ge, Lin; Hu, Ke‐jia; et al.
Abstracts: Protein Phosphatase Mg 2+ /Mn 2+ ‐Dependent 1K (PPM1K), also named as PP2Cm or branched‐chain α‐ketoacid dehydrogenase complex phosphatase, is a member of the metal‐dependent phosphatase family and an important metabolic regulator. Single nucleotide polymorphisms (SNPs) in PPM1K contributing to protein functional defects have been found to be associated with numerous human diseases, such as cardiovascular disease, maple syrup urine disease, type 2 diabetes, and neurological disease. PPM1K N94K is an identified missense mutant produced by one of the SNPs in the human PPM1K coding sequence. However, the effects of the N94K mutant on its activity and structural property have not been defined. Here, we performed a detailed enzymological study using steady‐state kinetics in the presence of pNPP or phospho‐peptide substrates and crystallographic analyses of the wild‐type and N94K PPM1K. The PPM1K‐N94K significantly impaired its Mg 2+ ‐dependent catalytic activity and structural analysis demonstrated that the N94K mutation induced a conformational change in the key residue in coordinating the Mg 2+ in the active site. Specifically, three Mg 2+ were located in the active site of the PPM1K N94K instead of two Mg 2+ in the PPM1K wild type. Therefore, our results provide a structure basis for the metal ion‐dependent PPM1K‐N94K phosphatase activity. Abstract : The crystallographic study disclosed that the N94K mutation caused the conformational change in the key residue in coordinating the Mg 2+ in the active site. Specifically, three Mg 2+ were located in the active site instead of the two Mg 2+ in the wild type. Our results provide a structure basis for the metal ion‐dependent PPM1K‐N94K phosphatase activity.